PERENCANAAN STRUKTUR GEDUNG KULIAH UTAMA FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO SEMARANG - Alextron Hutabarat; Arcito Bayu Praditya; Sri Tudjono; Ilham Nurhuda (Jurnal Karya Teknik Sipil, 2015)
A Multifunctional building to support learning activities has become an urgent need for the faculty of engineering of UNDIP as some departments have limited lecture rooms. The Construction of such building is a solution for better and comfortable lecture facilities at the Faculty of Engineering. The building structure is design as SRPMK or Special Moment Resisting Frame based on SNI 03-1726-2012 and SNI 03-2847-2002. The structure analysis and design of the building was conducted using a structural analysis program and Cad software. This thesis looks into structural design of Slabs, Beams, Columns, Lifts, Beam-Coloumn Joints, Tie Beam and Fondations.